Perceiving Ankara as a Place of Literary Memory Through Literary Museums - Ferah Burgul Adıgüzel (Ankara Araştırmaları Dergisi, 2020)
Places of literary memory include the literary past of a society and all kinds of meaning patterns. The function of literary memory places is to determine the state of all sorts of literary products and their creators, protect and immortalize them in order to prevent them from being forgotten. For example, the works of an author, the production process she/he underwent, and all events, people, etc. involved in her/his life during this process may fall within this scope. Ankara, as the subject of literary works, as the place where literary works were written, and as the home of authors living in it, can be defined as a place of literary memory. There are six literary museums in Ankara, where interactive activities can be conducted in line with the purpose and scope of literature education. Many educational or artistic interactive activities in literary museums facilitate the spread of literature education because they are implemented outside of school settings. In addition to supporting literature education, literary museums provide a collective perception of Ankara as a literary place through conveying the literary culture of the city. The purpose of this study is to encourage prospective Turkish language and literature teachers to perceive Ankara as a place of literary memory, as well as to raise their awareness in literary museums through the use of creative drama-based activities held in literary museums. The study was designed as a case study –a qualitative research design. Purposeful sampling method was used in the study. Data was collected through a semi-structured interview form, student diaries, and process evaluation notes/products. Descriptive analysis was used to analyze and interpret the data. The study concludes that the activities conducted in the literary museums in Ankara directly contributed to Ankara’s perception as a literary memory place, and that the literary memory of a city could be further developed with literary museums in that city as well as through interactive activities such as creative drama.